PERCEPTION AND ATTITUDINAL BEHAVIOR OF LECTURERS’ IN THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY TOOLS IN TEACHING/LEARNING IN MICHAEL OKPARA UNIVERSITY OF AGRICULTURE UMUDIKE - Joy C. OLOJEDE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study investigated perception and attitudinal behavior of lecturers in the use of ICT in classroom teaching and learning in Michael Okpara University of Agriculture, Umudike. A structured questionnaire was administered on a 5 point Likert-type questions to 120 of the 550 lecturers following simple random technique. The collected data were analyzed by finding means of respondents’ feelings and hypothesis with correlation coefficient. The means showed that ICT facilities are not frequently used in classroom teaching/learning by the lecturers (x̅ = 2.20). However, multimedia projector (x̅ = 3.49) and computer (x̅ = 3.36) were mostly used. The lecturers perception (x̅ = 3.05) was positive and their attitudinal behavior (x̅ = 2.89) was negative in the use of ICT in classroom. The correlation coefficient (r) was 0.373 and significant at 5% critical alpha level. It implies that there was a positive significant relationship between perception of ICT and attitude of the lecturers in the use of ICT. We advised that lecturers should put in more effort in the use of ICTs order than the multimedia and computer in classroom teaching/learning.